The Analysis Of Adjectives Tsurai, Kurushii And Kutsuu In Japanese Language Ruigigo - Wahyu, I Wayan Wahyu Cipta Widiastika; Ni Wayan Meidariani; Gede Timika Wijaya (SPHOTA: Jurnal Linguistik dan Sastra, 2023)
Japanese is a foreign language that has many variations of the lexicon. One of them is the lexicon variation in adjectives. This article discusses the analysis of the adjectives tsurai, kutsuhii and kutsuu in Japanese ruigigo. This study focuses on sentences used by native Japanese speakers. Data collection was carried out through interviews and note-taking techniques. The author conducts interviews directly with Japanese people while recording sentences containing 'tsurai, kutsuhii and kutsuu'. The data were analyzed using a contextual meaning theory approach (Pateda, 2010) by describing them in Japanese sentences. From the data found, the adjectives tsurai, kutsuhii and kutsuu have different meanings depending on the context of their usage. Based on the results of the analysis, in general (1) tsurai expressed a bitter experience, something uncomfortable, lazy to do something, (2) kutsuu stated difficult family conditions, difficult life, doing hard training), and (3) kutsuu expressed severe pain physical and mental discomfort and torture. The results of the study show that each lexicon of 'tsurai, kutsuhii and kutsuu' has almost the same meaning, namely painful or difficult, but has a slightly different usage in other activities.